2022
DOI: 10.4162/nrp.2022.16.5.658
|View full text |Cite
|
Sign up to set email alerts
|

Double burden of malnutrition in ethnic minority school-aged children living in mountainous areas of Vietnam and its association with nutritional behavior

Abstract: BACKGROUND/OBJECTIVES Although children of ethnic minority groups are experiencing a transition from a predominance of undernutrition to overnutrition, there is little evidence of a dual-malnutrition burden. Therefore, this study examined the double burden of malnutrition among school-aged ethnic minority children living in mountainous areas and its association with their diets. SUBJECTS/METHODS A cross-sectional study was conducted from September 2019 to March 2020 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nghiên cứu của Trương Thị Thùy Dương và cộng sự trên 1556 trẻ DTTS người Tày, Mường năm 2020 ghi nhận tỉ lệ suy dinh dưỡng thấp còi là 14% [5].…”
Section: Bàn Luận đặC đIểm Tăng Trưởng Và Dinh Dưỡngunclassified
“…Nghiên cứu của Trương Thị Thùy Dương và cộng sự trên 1556 trẻ DTTS người Tày, Mường năm 2020 ghi nhận tỉ lệ suy dinh dưỡng thấp còi là 14% [5].…”
Section: Bàn Luận đặC đIểm Tăng Trưởng Và Dinh Dưỡngunclassified
“…These children face barriers to receiving enough nutrition, access to healthcare, and availability of healthcare services. 4 Surveys show that the incidence of diarrhea in Cham children in Tan Chau Town during the annual flood season is relatively high, and the ability of families classified as poor or near-poor to access healthcare services is limited, which affects the nutritional status of children to some extent. [5][6][7] There is a crucial window of time for children's physical and behavioural development between the ages of 6 and 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The actual survey has shown that the work of preventing malnutrition is only well implemented in urban areas, while in remote, faraway, and ethnic minority areas, the rate of malnutrition in children is still high, among which children of minority ethnic groups suffer many disadvantages in nutrition care as well as health care and access to health care services. 4 The survey results show that the rate of children suffering from diarrhoea during the annual flood season is relatively high, while the access to healthcare services for families in the poor and near-poor categories is still limited, which somewhat affects the nutritional status of children. [5][6][7] The period from 6 to 24 months of age is a critical window for children to develop physically and behaviourally.…”
mentioning
confidence: 99%